Implementing Mycoplasma genitalium testing across a London-based sexual health service: A quality improvement project. (March 2020) - Khan, H; Alam, V; Yin, L; Tincknell, L; Wallis, E; Sethi, G
Recent national guidelines recommended testing for Mycoplasma genitalium (MG) in clinically-indicated conditions (CIC) including non-gonococcal urethritis (NGU), pelvic inflammatory disease (PID) and epididymo-orchitis. Over five months in 2018 a quality improvement project (QIP) was carried out across three London sexual health clinics with the aim of increasing MG testing rates in CICs. Three Plan-Do-Study-Act (PDSA) cycles were completed: improving IT access, an education event and reminder emails for clinicians who did not test in CIC. To measure testing rates ten patients from each CIC were randomly selected each week and MG testing outcomes were collected. As a balancing measure, we identified the rate of inappropriate MG testing. MG testing rates in patients with NGU increased to 90% following QIP initiation (baseline rate 60%) and this increase was sustained. No increase in MG testing was seen in PID and epididymo-orchitis. Inappropriate MG test rates were high (median of 11%) but remained constant throughout the QIP period. As MG testing is expanding across the UK, we outline a QIP integrating MG testing into a busy multi-site, sexual health service improving testing uptake while not increasing inappropriate testing.